2017
DOI: 10.9790/6737-04020609
|View full text |Cite
|
Sign up to set email alerts
|

Sports Specific Influence on Force Vital Capacity in University Players

Abstract: Abstract:Objective:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
1
0
1
Order By: Relevance
“…However, both VC and FVC in case of the basketball players and volleyball players varied significantly (p < 0.05) in comparison to the sedentary counterparts. In the Indian context, it has been reported that FVC of the Indian University volleyball players from the North Indian state of Haryana was significantly different in contrast to their sedentary counterparts [23]. However, the results of our study related to TV was in agreement with the report where it has been mentioned that in case of accomplished marathoners as well as other endurance trained athletes, the static lung volumes did not vary from the untrained individuals of comparable body size [24].…”
Section: Discussionsupporting
confidence: 91%
“…However, both VC and FVC in case of the basketball players and volleyball players varied significantly (p < 0.05) in comparison to the sedentary counterparts. In the Indian context, it has been reported that FVC of the Indian University volleyball players from the North Indian state of Haryana was significantly different in contrast to their sedentary counterparts [23]. However, the results of our study related to TV was in agreement with the report where it has been mentioned that in case of accomplished marathoners as well as other endurance trained athletes, the static lung volumes did not vary from the untrained individuals of comparable body size [24].…”
Section: Discussionsupporting
confidence: 91%
“…Some studies that don't see the effects of aerobic exercise to improved lung function viewed through the value of the vital capacity of the lungs and FEV1. Study from Malik et al (2017) explain the cause of the results insignificant can occur if there is possible bias of the control group where they significantly have higher BMI than with a group of aerobic athletes or anaerobic (Malik, 2017). Rakovac et al (2018) in Serbia, there is no difference in FVC values and FEV1 in the aerobics, anaerobic athlete group and non-athlete ccaused of a significant difference between anthropometric measurements in any group that make the appearance of bias (Rakovac, 2018).…”
Section: Resultsmentioning
confidence: 96%
“…Dentro de las pruebas atléticas más exigentes para entrenar y competir, se encuentra la carrera de fondo, ya que tanto las capacidades psíquicas como las físicas son particularmente esenciales para un buen desempeño deportivo 1 . Debido a la necesidad constante que se le presenta al deportista de sobreponerse a la fatiga y la relación que existe entre la sobrecarga que puede desestabilizar el equilibrio entre la oferta y la demanda de oxígeno a nivel miocárdico, es importante evaluar la función pulmonar, ya que esta juega un papel fundamental en el desempeño atlético 2 .…”
Section: Introductionunclassified